SISTEM MEKANIK DAN ELEKTRIK PADA PROTOTIPE ROBOT REHABILITASI KAKI - Novian Fajar Satria; Endah Suryawati Ningrum; Hernandi Firmansyah Putra (universitas teuku umar, 2020)
Stroke patients need rehabilitation to repair diseased parts of the body. Patients have limitations on therapists who have limitations and intensity to accompany the patient's rehabilitation process. The development of modern robotics technology provides solutions for independent consultations. This research has made a prototype of a rehabilitation robot with a mechanical design based on the foot rehabilitation movement reference as upper leg movement and lower leg movement. The movement is to bend and straighten the knee, and the movement of lifting and lowering the thigh. Mechanical adjustments to the movements applied make the prototype divided into several parts, namely asking the body, approving the legs and packing the actuator. The leg frame on the prototype has two free joints. The power system legs are built to complement the workings of the prototype and support the user's independent movement effort. The results of system testing that have been applied to this prototype are actuators that serve to assist users, provide user movement and provide additional power PWM motor used. Keywords— Stroke Patients, Rehabilitation Robot, Sistem Power Legs.